A Bit of Connexivity Around the Field of Ordinary Conditionals. Issue 2 (2nd April 2020) - Estrada-González, Luis; Ramírez-Cámara, Elisángela
ABSTRACT: In this brief note we explore a couple of features of the semantics for indicative conditionals provided by Field. Those features strikingly resemble some controversial principles in connexive logic. We will show that although Field's semantics has the technical means to stand to the mentioned features, more work is needed to make some of its outcomes less unintuitive.